Optimization Of Solvent Concentration And Extraction Time Of Chicken Eggshell Protein For Gel Peel-Off Face Mask Application Using Response Surface Methods - Ashari, Erin; Redjeki, Athiek Sri; Budiyanto, Budiyanto (Journal of Applied Sciences and Advanced Technology, 2024)
Chicken eggshells, commonly discarded as household and industrial waste, present a valuable opportunity for sustainable use due to their abundant quantity. This study explores the potential of utilizing chicken eggshells as a natural protein source to create eco-friendly skincare products, particularly peel-off gel masks, which can combat free radicals and enhance skin elasticity and moisture. The research focused on determining the optimal conditions for protein extraction from chicken eggshells using acetic acid solvent and varying extraction times. Response Surface Methodology (RSM) was employed to optimize these conditions. The protein extraction process involved testing the extracted protein for biuret reaction using spectrophotometry, determining protein content with Ultra Performance Liquid Chromatography (UPLC), and evaluating the physical properties of the resulting peel-off gel mask. The results indicated that both solvent concentration and extraction time significantly impact the yield of protein. The optimal conditions were found to be an acetic acid concentration of 0.5 M and an extraction time of 24 hours, which produced a yield of 5.064%. The RSM model validation showed a p-value 0.05, a desirability index of 0.887, and a predicted yield of 3.080%, with a deviation of 1.98% from the actual yield. These findings suggest that the model is accurate and reliable for further development of the peel-off gel mask. This approach not only provides a sustainable use for eggshell waste but also contributes to the development of high-quality, natural skincare products.